The use of outcome measures relating to the knee - Beard, D; Knezevic, K; Al-Ali, S; Dawson, J; Price, A (2010)
Accurate outcomes assessment is one of the fundamental aspects of any reliable research. There are a vast number of outcome instruments currently available in orthopaedics. This plethora and diversity can lead to frustration when it comes to choosing the appropriate option. In this article we address the essential properties an outcome measure must possess, aiming to allow an informed selection of the most suitable instrument. We describe and illustrate key psychometric properties that are to be assessed when judging suitability of an instrument, such as validity, reliability and responsiveness. We also review some of the most commonly used and recommended outcome measures available in regard to different knee pathologies. With no intention of recommending a specific option, we briefly outline advances and shortcomings of named instruments. © 2010 Elsevier Ltd.